The Role of Education in Influencing Capital Markets’ Liquidity in the CEE Countries - Ela-Andrada Puscasu (Revista de Studii Financiare)
Capital markets serve an essential role in the efficient allocation of resources in an economy, with their liquidity and stability being critical indicators of operational efficiency. The influence of education in cultivating financial literacy, shaping investment behaviours, and thereby promoting market efficiency, financial development, and sustainable economic growth, is increasingly becoming the focus of research in this field. This study specifically explores the relationship between education levels and capital market liquidity in the Central and Eastern European countries across the period 2013-2021 via a panel regression methodology. Our findings show a significant relationship between education and enhanced capital market liquidity, highlighting the importance of investing in both primary and secondary education to improve market efficiency. Primary education enrollment seems to exert a negative impact on market spread and illiquidity, while secondary enrollment is associated with a diminishing effect on market spread. These patterns persist for both male and female enrollment alike. By furthering the understanding of the association between education and capital market activity, this research paper extends the current studies in this domain and reinforces the idea that education plays an instrumental role in capital market liquidity. This adds to the body of knowledge on the role of education in influencing capital market activity and offers a nuanced view of its impact on market liquidity in the CEE region.